Recent Efforts to Prevent Undesirable Reactions From Fractionation to Depolymerization of Lignin: Toward Maximizing the Value From Lignin - Kim, Kwang Ho; Kim, Chang Soo (Frontiers in Energy Research, 2018)
Lignin is a major component of lignocellulosic biomass along with cellulose and hemicellulose, currently underutilized with the bulk of technical lignin being combusted for heat generation in plant. From the technoeconomic perspective, the success of a future biorefinery is highly dependent on lignin valorization. However, structural complexity, heterogeneity of lignin, and several undesirable reactions associated with the nature of lignin and process conditions obstruct the effective utilization of lignin. Lignin condensation has been a long-lasting problem from conventional to recent biorefineries, which makes the recovered lignin more difficult to decompose. Also, the undesirable condensation and repolymerization during the depolymerization of lignin is more problematic as this significantly limits its ability to be depolymerized to low molecular weight products at high yields. To solve this problem, which ultimately enables maximizing lignin utilization, there have been many efforts in various aspects. In this review, we focus on the undesirable reactions occurring during the fractionation and depolymerization process of lignin and introduce recent efforts to suppress or minimize those unwanted reactions. The aim of all these efforts is to maximize lignin conversion to low molecular weight products.